EFFECT OF DIFFERENT CONCENTRATIONS OF BENZYLAMINOPURINE ON THE MICROPROPAGATION OF TWO VARIETIES OF NATIVE CHILI (Capsicum chinense Jacq.) IN PUCALLPA - VILLEGAS-PANDURO, Pablo Pedro (2021)
The effect of different concentrations of Benzylaminopurine (BAP) on the micropropagation of native chili (sweet chili and pucunucho chili) was verified. Seeds were disinfected with 2 % sodium hypochlorite for 30 minutes, rinsed with sterile distilled water and sown in culture medium with salts and vitamins from Murashige & Skoog, supplemented with 30 g L-1 of sucrose, 11 g L-1 of agar and without growth regulators. After 45 days of in vitro development, the seedlings were transferred to Murashige & Skoog medium, adding different concentrations of BAP (0 ppm, 0.5 ppm, 1 ppm and 1.5 ppm). It is concluded that the sanitization of the seeds of sweet chili and pucunucho chili with 2 % sodium hypochlorite for 30 minutes generated 100 % of healthy seeds. The concentrations of BAP studied were effective for the increase in the length of stems, number of roots, number of leaves, nodes and callus formation in sweet chili seedlings. On the other hand, for the seedlings of pucunucho chili, the increase in the number of leaves, nodes and roots occurred in the absence of concentrations of BAP, except for the generation of callus tissue.